Le XVIIIe siècle et les décrets de Nueva Planta : accommodement et dissidence - Joaquim Albareda Salvadó (Catalonia)
After the Catalan defeat of 1714, as time went by and thanks to the economic growth and increasing involvement in the Spanish and Latin American markets, the Catalans adapted to the Bourbon regime. However, how does the image of a prosperous Catalonia, of which foreign travelers inevitably speak during the 18th century, and that the historian Pierre Vilar described in a splendid manner, fit into the story of a heavy repression by the Bourbons? In spite of that, the examples of politic dissidence —together with the chronic mistrust by the Bourbon authorities— will not end at the end of the century. Thus, one can conclude that the memory of the Catalan freedom and the determined manner of organizing the res publica will persist at the end of the 18th century, not conform to the dictates of the Bourbon absolutism.